Project Manager's comment on adding drawings of elevator switch box and wiring tube of BRAC University new campus project - BUCG-ABC Joint Venture (Brac University, 2023)
This record consists of general correspondence regarding Project Manager's comment on adding drawings of elevator switch box and wiring tube of BRAC University new campus project.